Enhancing Thermal Stability and Bioaccesibility of Açaí Fruit Polyphenols through Electrohydrodynamic Encapsulation into Zein Electrosprayed Particles - Carol López de Dicastillo; Constanza Piña; Luan Garrido; Carla Arancibia; María José Galotto (MDPI AG, 2019)
The açaí fruit (Euterpe oleracea Mart.) is well known for its high content of antioxidant compounds, especially anthocyanins, which provide beneficial health properties. The incorporation of this fruit is limited to food products whose processing does not involve the use of high temperatures due to the low thermal stability of these functional components. The objective of this work was the encapsulation of açaí fruit antioxidants into electrosprayed zein, a heat-resistant protein, to improve their bioavailability and thermal resistance. First, the hydroalcoholic açaí extract was selected due to its high polyphenolic content and antioxidant capacities, and, subsequently, it was successfully encapsulated in electrosprayed zein particles. Scanning electron microscopy studies revealed that the resulting particles presented cavities with an average size of 924 nm. Structural characterization by Fourier transform infrared spectroscopy revealed certain chemical interaction between the active compounds and zein. Encapsulation efficiency was approximately 70%. Results demonstrated the effectiveness of the encapsulated extract on protecting polyphenolic content after high-temperature treatments, such as sterilization (121 °C) and baking (180 °C). Bioaccesibility studies also indicated an increase of polyphenols presence after in vitro digestion stages of encapsulated açaí fruit extract in contrast with the unprotected extract.